Prevalence and predictors of depression among hemodialysis patients: a prospective follow-up study - Amjad Khan; Amer Hayat Khan; Azreen Syazril Adnan; Syed Azhar Syed Sulaiman; Saima Mushtaq (BMC Public Health, 2019)
Abstract Background Even though depression is one of the most common psychiatric disorders, it is under-recognized in hemodialysis (HD) patients. Existing literature does not provide enough information on evaluation of predictors of depression among HD patients. The objective of the current study was to determine the prevalence and predictors of depression among HD patients. Methods A multicenter prospective follow-up study. All eligible confirmed hypertensive HD patients who were consecutively enrolled for treatment at the study sites were included in the current study. HADS questionnaire was used to assess the depression level among study participants. Patients with physical and/or cognitive limitations that prevent them from being able to answer questions were excluded. Results Two hundred twenty patients were judged eligible and completed questionnaire at the baseline visit. Subsequently, 216 and 213 patients completed questionnaire on second and final follow up respectively. The prevalence of depression among patients at baseline, 2nd visit and final visit was 71.3, 78.2 and 84.9% respectively. The results of regression analysis showed that treatment given to patients at non-governmental organizations (NGO’s) running HD centers (OR = 0.347, p-value = 0.039) had statistically significant association with prevalence of depression at final visit. Conclusions Depression was prevalent in the current study participants. Negative association observed between depression and hemodialysis therapy at NGO’s running centers signifies patients’ satisfaction and better depression management practices at these centers.